2017
DOI: 10.1002/ejlt.201700130
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Oils Acting as Encapsulated Bioactives and Costabilizers in Miniemulsion Polymerization Reactions

Abstract: Vegetable oils with different chemical structures are successfully encapsulated and applied as costabilizers in miniemulsion polymerization reactions. The results are compared to hexadecane, a well-known costabilizer used for this type of polymerization. The great advantage of using vegetable oils is that besides acting as costabilizers, they are also encapsulated, increasing the application of the nanoparticles. Results show that kinetics tend to be slower with argan oil, due to the higher concentration of do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…[ 35 ] When incorporating coconut oil as a co‐stabilizer in the mini‐emulsion polymerization of MMA, Bigon et al also showed a reduction in the average weighted molecular weight ( M w ) from 20.05 × 10 5 g mol –1 to 18.56 × 10 5 g mol –1 and an increase in the polydispersity from 1.619 to 1.822, compared to the experiments in which hexadecane was used as a co‐stabilizer. [ 38 ] Bathfield et al also observed a reduction in the polymer molecular weight when incorporating triglycerides as co‐stabilizers in the vinyl acetate miniemulsion polymerization in comparison to the experiments in which only hexadecane was used as co‐stabilizer. [ 36 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 35 ] When incorporating coconut oil as a co‐stabilizer in the mini‐emulsion polymerization of MMA, Bigon et al also showed a reduction in the average weighted molecular weight ( M w ) from 20.05 × 10 5 g mol –1 to 18.56 × 10 5 g mol –1 and an increase in the polydispersity from 1.619 to 1.822, compared to the experiments in which hexadecane was used as a co‐stabilizer. [ 38 ] Bathfield et al also observed a reduction in the polymer molecular weight when incorporating triglycerides as co‐stabilizers in the vinyl acetate miniemulsion polymerization in comparison to the experiments in which only hexadecane was used as co‐stabilizer. [ 36 ]…”
Section: Resultsmentioning
confidence: 99%
“…Shorter polymer chains need less energy to promote their mobility, which reduces the glass transition temperature. [ 38 ] Other important fact that contributes to the reduction of T g is the plasticizer effect promoted by propolis compounds due to their lipophilic characteristic.…”
Section: Resultsmentioning
confidence: 99%
“…Vegetable oils can effectively replace the organic solvents as the continuous phase in the inverse emulsion. Plant-based oils exemplify a perfectly renewable resource, as they are not miscible with water; therefore, they can be exploited to prepare new polymer products in dispersed systems. , Vegetable oils comprise triacylglycerols composed of three fatty acids bound to a glycerol backbone, whose structure depends on the plant source. Triglycerides bear several reactive sites, including double bonds and ester groups, opening up opportunities to customize new structures . In addition, vegetable oils were successfully applied as emulsion costabilizers . Interestingly, the industry frequently implements emulsion systems based on vegetable oils, specifically in designing cutting fluids , and diesel engine fuels …”
Section: Introductionmentioning
confidence: 99%
“…45 In addition, vegetable oils were successfully applied as emulsion costabilizers. 46 Interestingly, the industry frequently implements emulsion systems based on vegetable oils, specifically in designing cutting fluids 43,47 and diesel engine fuels. 48 In this contribution, several types of vegetable oils − rapeseed and sunflower oil, extra-virgin olive oil, and extravirgin avocado oil, were used for the first time as a continuous phase in the polymerization of 2-hydroxyethyl acrylate (HEA) via ARGET ATRP in an inverse emulsion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Miniemulsion polymerization is an in situ encapsulation technique, where polymer synthesis and encapsulation of the component of interest are performed in a single step [7]. Some authors have evaluated the use of alternative co-stabilizers, such as andiroba oil [8,9]; jojoba oil [8]; clove oil [10]; sunflower seed oil and linoleic acid [11]; linseed oil [9]; argan oil and coconut oil [12], being encapsulated as compounds of interest besides stabilizing the miniemulsion.…”
Section: Introductionmentioning
confidence: 99%